ANALISIS KUANTITATIF KECELAKAAN LALU LINTAS DI AMERIKA SERIKAT PADA TAHUN 2000-2023 MENGGUNAKAN STATISTICAL QUALITY CONTROL - IDA AYU OKTAVIANTI; ZAKIA ALYA ALYA ROSYDA; KEZIA BRILLIANT NAZARENA; NI WAYAN RUSNIATI; MADE AYU DWI OCTAVANNY (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Traffic accidents are a critical issue in road safety and public health in the United States. This study examines the patterns and statistical stability of annual traffic accidents from 2000 to 2023 using a Statistical Quality Control (SQC) approach. Secondary data were obtained from official publications of the National Highway Traffic Safety Administration (NHTSA), including accident severity, numbers of fatalities and injuries, population size, and risk indicators. The analysis employed five of the seven basic SQC tools, namely check sheets, histograms, Pareto diagrams, control charts (p-charts and u-charts), and cause-and-effect diagrams. The results show that property damage only accidents dominate total crash occurrences, while fatal crashes represent a small proportion but lead to significant loss of life. Control chart analysis indicates statistical instability in the proportion of fatal crashes and fatality rates, suggesting the presence of special causes rather than random variation. Overall, the findings highlight the usefulness of SQC as an effective tool for monitoring traffic safety performance and identifying critical variations requiring targeted interventions.